Determination of Physicochemical Properties of Some Selected Well and Borehole Water of Nasarawa Area of Zagga Town of Kebbi State, Nigeria - Yusuf Sarkingobir; Asiya Gidado Yabo (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2022)
Nowadays, especially in poor resource settings, there is rising infectious and chronic diseases, which most especially can be attributed to poor water quality as one of the causes. Consequently, it becomes imperative to determine the safety of drinking water source. This research is aimed to determine the physicochemical characteristics in well water and borehole water in Nasarawa area of Zagga town of Kebbi state, using standard methods and materials of analytical grade. Results show the pH range of 6.13-6.7, and conductivity is in the range of 3.37-80.1 (ppm). Bicarbonate determined is within the range of 24-84 (ppm). TDS was found in the range of 9-35(ppm), while DO found was 4.7-6.8 (ppm). Chloride was 0.7-11.3 (ppm), and TSS is 7.3-13.3 (ppm). pH, DO, Cl, TDS, and bicarbonate are within the World Health Organization (WHO) permissible limits as found in the findings of this study.